Dampak Penerapan Agreement On The Application Of Sanitary And Phytosanitary Measures Terhadap Perdagangan Di Indonesia - Fahmi Fairuzzaman (Lex Renaissance, 2018)
The problem in this research is whether the SPS Agreement actually becomes a barrier in trade? And what is the impact of the SPS Agreement on trade in Indonesia? The research method used is Normative Juridical. The results of the study concluded, first, the existence of the SPS Agreement can be a barrier to trade, but it is an obstacle that is excluded as long as it is done in accordance with the provisions contained in the SPS Agreement. Second, the existence of the SPS Agreement allows Indonesia to implement regulations that better protect its citizens from health risks that may arise from the import of certain products, especially food. These rules must still be in line with the SPS Agreement.